The Role of Single Fathers in Shaping the Character of Junior High School Students - Hanan, Ruina Adzra; Putri, Olivia Dwi Marliana; Khumayah, Siti; Erawati, Dedet (Journal of Comprehensive Science, 2025)
Recently, divorce cases in Indonesia have increased following the Covid-19 pandemic that hit Indonesia between 2019 and 2022. This research aims to analyze the role of single fathers in shaping the character of children in junior high school (SMP). The primary focus of this research is to understand how emotional involvement, closeness in daily activities, motivation, modeling, and communication patterns established by single fathers significantly influence the process of character development in children. The method used is a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation. The informants in this research consist of single fathers, students, guidance counselors (BK/Bimbingan Konseling), and child psychologists at the BPK Penabur School in Cirebon City. The theory used is Robert K. Merton's Social Role Theory. The results of the research indicate that a father's active involvement in a child's life impacts the development of character traits such as responsibility, empathy, and discipline. Therefore, it can be concluded that a father's presence in daily routines and open communication create a sense of security and emotional attachment, despite challenges in terms of children's expression of feelings. Consistency in parenting is a crucial element in supporting children's psychological and social development.